2017
DOI: 10.1177/1932296817704442
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Management Using Smart Mobile Telemedicine

Abstract: Gestational diabetes (GDM) burden has been increasing progressively over the past years. Knowing that intrauterine exposure to maternal diabetes confers high risk for macrosomia as well as for future type 2 diabetes and obesity of the offspring, health care organizations try to provide effective control in spite of the limited resources. Artificial-intelligence-augmented telemedicine has been proposed as a helpful tool to facilitate an efficient widespread medical assistance to GDM. The aim of the study we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 18 publications
1
85
0
2
Order By: Relevance
“…The system, which is based on the application of a natural language processing (NLP) algorithm, was validated during the postpartum visits of 600 GDM patients. Rigla et al also investigated tools for GDM patients [ 133 ]. They proposed a mobile app based on an AI-augmented telemedicine DSS as a tool for helping GDM patients.…”
Section: Resultsmentioning
confidence: 99%
“…The system, which is based on the application of a natural language processing (NLP) algorithm, was validated during the postpartum visits of 600 GDM patients. Rigla et al also investigated tools for GDM patients [ 133 ]. They proposed a mobile app based on an AI-augmented telemedicine DSS as a tool for helping GDM patients.…”
Section: Resultsmentioning
confidence: 99%
“…A previous systematic review concluded that there was insufficient evidence showing that the use of telemedicine technology was superior to the use of the standard care procedure for women with GDM [ 39 ]. Riga et al [ 40 ] reported promising results with regard to the acceptance of mobile phone telemedicine among pregnant women with GDM. However, little is known about the use of mobile phone apps for the management of GDM [ 25 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review concluded that there is currently insufficient evidence that telemedicine technology is superior to standard care for women with GDM [33]. Riga et al found promising results regarding the acceptance of smart mobile telemedicine for pregnant women with GDM [34]. Little is known about the use of smartphone apps for the management of GDM [22,35].…”
Section: Discussion Principal Resultsmentioning
confidence: 99%